Nitrogen fertilization rates mediate rhizosphere soil carbon emissions of continuous peanut monoculture by altering cellulose-specific microbess - Wu, Zhengfeng; Tang, Zhaohui; Yu, Tianyi; Zhang, Jiancheng; Zheng, Yongmei; Yang, Jishun; Wu, Yue; Sun, Qiqi (Frontiers in Plant Science, 2023)
Crops influence both soil microbial communities and soil organic carbon (SOC) cycling through rhizosphere processes, yet their responses to nitrogen (N) fertilization have not been well investigated under continuous monoculture. In this study, rhizosphere soil microbial communities from a 5-year continuous mono-cropped peanut land were examined using Illumina HighSeq sequencing, with an N fertilization gradient that included 0 (N0), 60 (N60), 120 (N120) and 180 (N180) kg hm−2. Soil respiration rate (Rs) and its temperature sensitivity (Q10) were determined, with soil carbon-acquiring enzyme activities assayed. The obtained results showed that with N fertilization, soil mineral N (Nmin) was highly increased and the soil C/N ratio was decreased; yields were unchanged, but root biomass was stimulated only at N120. The activities of β-1,4-glucosidase and polyphenol oxidase were reduced across application rates, but that of β-1,4-cellobiohydrolase was increased only at N120. Bacterial alpha diversity was unchanged, but fungal richness and diversity were increased at N60 and N120. For bacterial groups, the relative abundance of Acidobacteria was reduced, while those of Alphaproteobacteria and Gammaproteobacteria were increased at N60 and N120. For fungal members, the pathogenic Sordariomycetes was inhibited, but the saprotrophic Agaricomycetes was promoted, regardless of N fertilization rates. RDA identified different factors driving the variations in bacterial (root biomass) and fungal (Nmin) community composition. N fertilization increased Rs slightly at N60 and significantly at N120, mainly through the promotion of cellulose-related microbes, and decreased Rs slightly at N180, likely due to carbon limitation. N fertilization reduced microbial biomass carbon (MBC) at N60, N120 and N180, decreased SOC at N120 and N180, and suppressed dissolved organic carbon (DOC) at N180. In addition, the unchanged Q10 may be a joint result of several mechanisms that counteracted each other. These results are of critical importance for assessing the sustainability of continuously monocultured ecosystems, especially when confronting global climate change.